Assessment of myofiber microstructure changes due to atrophy and recovery with time‐dependent diffusion MRI. (18th May 2021) - Lemberskiy, Gregory; Feiweier, Thorsten; Gyftopoulos, Soterios; Axel, Leon; Novikov, Dmitry S.; Fieremans, Els
Abstract : Current clinical MRI evaluation of musculature largely focuses on nonquantitative assessments (including T1‐, T2‐ and PD‐weighted images), which may vary greatly between imaging systems and readers. This work aims to determine the efficacy of a quantitative approach to study the microstructure of muscles at the cellular level with the random permeable barrier model (RPBM) applied to time‐dependent diffusion tensor imaging (DTI) for varying diffusion time. Patients ( N  = 15, eight males and seven females) with atrophied calf muscles due to immobilization of one leg in a nonweight‐bearing cast, were enrolled after providing informed consent. Their calf muscles were imaged with stimulated echo diffusion for DTI, T1‐mapping and RPBM modeling. Specifically, After cast removal, both calf muscles (atrophied and contralateral control leg) were imaged with MRI for all patients, with follow‐up scans to monitor recovery of the atrophied leg for six patients after 4 and 8 weeks. We compare RPBM‐derived microstructural metrics: myofiber diameter, a, and sarcolemma permeability, κ, along with macroscopic anatomical parameters (muscle cross‐sectional area, fiber orientation, < θ >, and T1 relaxation). ROC analysis was used to compare parameters between control and atrophied muscle, while the Friedman test was used to evaluate the atrophied muscle longitudinally. We found that the RPBM framework enables measurement of microstructural parameters from diffusion time‐dependent DTI, of which the myofiber diameter is a stronger predictor of intramuscular morphological changes than either macroscopic (anatomical) measurements or empirical diffusion parameters. This work demonstrates the potential of RPBM to assess pathological changes in musculature that seem undetectable with standard diffusion and anatomical MRI. Abstract : We acquired STEAM DWI to image the calf muscles of 15 patients with atrophied calf muscles, due to immobilization of one leg in a nonweight‐bearing cast. Microstructural parameters (derived from RPBM), such as myofiber diameter, a, and membrane permeability, κ, and macroscopic parameters, cross‐sectional area, T1 and fiber orientation, were evaluated in their efficacy to detect changes due to atrophy and recovery over longitudinal scans. We found that a was the strongest predictor of both atrophy and recovery.